Correction: Adsorption of PAHs on interstellar ice viewed by classical molecular dynamics. Issue 16 (6th April 2018) - Michoulier, Eric; Noble, Jennifer A.; Simon, Aude; Mascetti, Joëlle; Toubin, Céline
Abstract : Correction for 'Adsorption of PAHs on interstellar ice viewed by classical molecular dynamics' by Eric Michoulier et al., Phys. Chem. Chem. Phys., 2018, DOI: ;10.1039/c8cp00593a .